HAK ASASI DALAM PERLEMBAGAAN MALAYSIA: RUANG LINGKUP DAN MASALAHNYA - Bari, Abdul Aziz (Jurnal Syariah, 2019)
This essay seeks to arrive at several generalisation on the nature and implementation of the provisions under Pan Tho of the Federal Constitution of Malaysia which codifies the essentially human rights provisions. Given the objective the anicle will not confine itself to just the law but will also look at the practice which includes the co un decisions as well as the way the government agencies like the police force view and exercise their powers. The problems and weaknesses of protecting human rights in Malaysia are rooted in various reasons. These include the philosophical foundations laid down by Reid Commission Repon as well as the attitude of the people in general. The latter is imponant as it influences the way the powers-that-be treat the provisions penaining to fundamentalliberties. The establishment of National Human Rights Commission in 1999 underlined this although its functioning thus far has not been entirely satisfactory. The position of Islam and the muslims is another concern of this essay. This question has not been dealt with satisfactorily by the couns and this may alarm the majority of the population who feel that Islam has a special place in the constitutional structure.